Efectos del láser MLS® como herramienta moduladora en el manejo de heridas en felinos - Pérez Capa, Maria Gabriela (Machala : Universidad Técnica de Machala, 2025)
Canine cardiopulmonary dirofilariasis caused by Dirofilaria immitis is an emerging zoonosis of increasing relevance in tropical and coastal regions. This study aimed to determine the presence of the parasite in dogs from the cantons of Machala, Santa Rosa, and Huaquillas, in El Oro Province, Ecuador, using a combined approach of immunodiagnostics, PCR, and phylogenetic analysis. A total of 40 dogs with compatible clinical or epidemiological backgrounds were evaluated using a rapid immunochromatographic (IC) antigen test as an initial screening tool. Of these, 24 dogs (60%) tested positive by IC; however, endpoint PCR targeting the mitochondrial COI gene confirmed infection in only 10 cases (41.7%), revealing potential false-positive serological reactions. Chi-square statistical analysis showed a significant association between PCR results and canton of origin (p < 0.001), with Machala exhibiting the highest proportion of positive cases. No significant relationship was observed with sex (p = 1.00) or individual age (p = 0.212). Sanger sequencing of PCR amplicons and comparison with GenBank sequences confirmed D. immitis with 100% identity. Phylogenetic analysis demonstrated low genetic diversity, clustering within haplotypes shared with strains reported from Europe, North America, and Asia. These findings confirm active circulation of D. immitis in El Oro Province and highlight the need for surveillance and control strategies under a One Health framework. Furthermore, the study demonstrates the value of molecular diagnostics as a complementary tool to improve epidemiological accuracy and reduce false-positive outcomes.
El presente estudio evaluó los efectos del láser MLS® (Multiwave Locked System) como herramienta moduladora en el proceso de cicatrización de heridas en felinos, mediante un diseño observacional, descriptivo y longitudinal aplicado en dos casos clínicos atendidos en Machala, Ecuador. Los pacientes presentaron heridas de distinta etiología: una crónica con infiltrado eosinofílico y otra traumática infectada. Se aplicaron protocolos de fotobiomodulación con dosis iniciales de 3–5 J/cm2, tres sesiones por semana, complementados con terapias convencionales locales y sistémicas. Los resultados mostraron una reducción significativa del área de la herida (60 % en 21 días y hasta 100 % en 28–56 días según el caso), acompañada de disminución del dolor y resolución del proceso inflamatorio. En el caso crónico, el láser MLS® moduló la respuesta inmunológica, reduciendo infiltrados eosinofílicos y mediadores proinflamatorios, lo que facilitó una cicatrización organizada y disminuyó el riesgo de recidivas. Estos hallazgos confirman al láser MLS® como una alternativa terapéutica no invasiva, segura y eficaz frente a las limitaciones de antibióticos y corticosteroides, contribuyendo a la mejora del bienestar animal y a la adherencia de los tutores. Aunque la muestra reducida limita la generalización de resultados, la investigación aporta evidencia clínica preliminar que valida la integración de la fotobiomodulación en protocolos terapéuticos de medicina veterinaria en felinos.
Keywords: LÁSER MLS; FOTOBIOMODULACIÓN; HERIDAS FELINAS; EOSINOFILIA